2014
DOI: 10.1159/000366292
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Metastases of Renal Cell Carcinoma Revealed by Syncope: Diagnosis and Treatment

Abstract: Introduction: Cardiac metastases from renal cell carcinoma are very rare. In this report, we describe a case of ventricular metastases in the absence of vena cava or right atrial involvement. Case Report: We report the case of a 60-year-old man who had a past history of heavy tobacco intake and well-controlled arterial hypertension. He experienced sudden-onset palpitations, lost consciousness and, as a result, was involved in an accident on the public highway. Cardiac arrhythmia was suspected and, therefore, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 6 publications
0
9
0
2
Order By: Relevance
“…Since signs and symptoms of metastatic cardiac involvement can be non-specific, a high index of suspicion is required for diagnosis. It is frequently a post-mortem finding [ 2 ]. Also, cardiac metastases can be mistaken for thrombi, endocarditis, or primary tumors, therefore echocardiograms can be limiting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since signs and symptoms of metastatic cardiac involvement can be non-specific, a high index of suspicion is required for diagnosis. It is frequently a post-mortem finding [ 2 ]. Also, cardiac metastases can be mistaken for thrombi, endocarditis, or primary tumors, therefore echocardiograms can be limiting.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Schinzari et al showed a partial response with signs of metastatic devascularization with pazopanib [ 5 ]. Bazine et al showed stabilization of cardiac metastases with sunitinib [ 2 ]. Stellato et al showed partial regression of metastases with cabozantinib after a 3-month treatment period [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extremely rare are intramyocardial metastasis without venous involvement. They may be asymptomatic but can manifest as a cardiac arrhythmia or longer QTc interval [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment for metastatic RCC is challenging and may include systemic therapy with immunotherapy and/or molecularly targeted therapy, cytoreductive nephrectomy, metastasectomy, or clinical trial enrollment (6)(7)(8)(9). Typical sites of metastases include the lymph nodes, lung, bone, liver, and brain (10)(11)(12). Other rare sites of metastases include the head and neck, skin, skeletal muscle, and pelvis (13).…”
Section: Introductionmentioning
confidence: 99%